1990
DOI: 10.1111/j.1365-2842.1990.tb00014.x
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary electromyographic study of bite force and jaw‐closing muscle fatigue in human subjects with advanced tooth wear

Abstract: The maximum bite force was recorded in five experimental volunteers with advanced tooth wear and five control volunteers who showed no abnormal wear. All subjects were then asked to maintain a force of 50% of the maximum for as long as possible while surface electromyograms from the masseter and temporalis muscles were recorded. The bite force and endurance time were found to be slightly increased in the experimental group, but no conclusions could be drawn regarding the state of fatigue. Two significant probl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
27
4
11

Year Published

1993
1993
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 9 publications
6
27
4
11
Order By: Relevance
“…This result confirms the concept of the fracture resistance of endodontically treated roots is directly affected by remaining radicular dentin thickness at the cervical portion of the roots [51]. …”
Section: Discussionsupporting
confidence: 88%
“…This result confirms the concept of the fracture resistance of endodontically treated roots is directly affected by remaining radicular dentin thickness at the cervical portion of the roots [51]. …”
Section: Discussionsupporting
confidence: 88%
“…The mean fracture resistance results observed in the present study (Table 2) are higher than the mean bite force values reported by Lyons 15 (1990) for canine teeth of approximately 22 kgf. In contrast, patients with bruxism presented a bite force of almost 26 kgf and the maximum bite force in the canine region ranged from 32 to 35 kgf.…”
Section: Discussioncontrasting
confidence: 78%
“…The bite force meter, which has been described previously (Lyons & Baxendale, 1990), was placed between the second premolar and first molar teeth on the preferred chewing side. The volunteers were then asked to maintain 50% MVC for as long as possible, using force displayed on an oscilloscope screen for visual feedback.…”
Section: Methodsmentioning
confidence: 99%